Higher index Fano varieties with finitely many birational automorphisms. Issue 11 (2nd November 2022) - Chen, Nathan; Stapleton, David
Abstract : A famous problem in birational geometry is to determine when the birational automorphism group of a Fano variety is finite. The Noether–Fano method has been the main approach to this problem. The purpose of this paper is to give a new approach to the problem by showing that in every positive characteristic, there are Fano varieties of arbitrarily large index with finite (or even trivial) birational automorphism group. To do this, we prove that these varieties admit ample and birationally equivariant line bundles. Our result applies the differential forms that Kollár produces on $p$ -cyclic covers in characteristic $p > 0$ .